Olimpiiskie igry i ranee khristyanstvo - Rekutina, N. V. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The facts, shown by the author, give the basis to consider, that the consideration of the question about the discontinuance of the Olympic games and others periodic agons in Hellas is in direct dependence from concrete edict of Feodosiya and it is not the one possible version of the considered events. The Olympic and others agons of Greece could exist separately from sacrifice processions and others ceremonies of the heathenish cult. The similar phenomenon is known in Antiohy, where the games carrying the name Olympic, were carried out till 520 year.